Image Processing and Communications Challenges 8 8th International Conference, IP&C 2016 Bydgoszcz, Poland, September 2016 Proceedings - Choraś, Ryszard S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book collects a series of research papers in the area of Image Processing and Communications which not only introduce a summary of current technology but also give an outlook of potential feature problems in this area. The key objective of the book is to provide a collection of comprehensive references on some recent theoretical development as well as novel applications in image processing and communications. The book is divided into two parts and presents the proceedings of the 8th International Image Processing and Communications Conference (IP&C 2016) held in Bydgoszcz, Poland September 7-9 2016. Part I deals with image processing. A comprehensive survey of different methods of image processing, computer vision is also presented. Part II deals with the telecommunications networks and computer networks. Applications in these areas are considered.
Keywords: Computational intelligence; Artificial intelligence; Signal processing; Telecommunication; Computational Intelligence; Artificial Intelligence; Signal, Speech and Image Processing; Communications Engineering, Networks